(untitled) (Global Journal of Human-Social Science, 2025)
After 31 July in 1995 Mobile Revolution in India, as a technological advancement in communication, the media landscape has witnessed a revolutionary transformation, linking the information system to a new trajectory of development. The present research article, with a focus on Media Participatory Theory and Development Communication Theory, examines the influence of the uses of mobile phones as tools for active participation in community media. If we consider community media, it is often viewed as a tool for development. In this context, the use of mobile phones as a powerful medium for community participation and development can significantly enhance engagement within community media. By leveraging mobile technology, community participation in media can be strengthened, fostering greater inclusivity and developmental impact. This research paper explores how mobile phone-based applications for social media platforms facilitate the transformation of community media participation from passive engagement to active involvement. The study is grounded in participatory media and development communication theories, emphasizing the role of digital tools in enhancing community participation and fostering meaningful engagement.